THE IMPLEMENTATION OF MERDEKA CURRICULUM IN MAKASSAR SOUTH SULAWESI: EFL ISLAMIC SCHOOL TEACHERS’ PERCEPTIONS - Said, Amri Amsyari; Amirullah, Amirullah; Baa, Sultan (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
This research aimed at finding out EFL Islamic School teachers' perceptions toward the implemention of Merdeka Curriculum in their schools. This reasearch applied case study research design. Two Islamic Schools in Makassar South Sulawesi were selected as subject of the study. Five EFL teachers of those schools were selested as participants of the study using purposive sampling technique. Those teachers were asked about their perceptions related to their readiness in implementing Merdeka Curriculum, their challenges in implementing the Merdeka Curriculum, and their suggestions on the challenges in implementing Merdeka Curriculum in their schools. The data then analysed using Miles and Huberman qualitative data analysis. The research results showed: 1) Most of the teachers were ready to implement the Merdeka Curriculum in their schools, which can be seen from the readiness of creating lesson planning, learning processes, and assessment; 2) The challenges faced by EFL teachers in Islamic schools include: disparate grasp of the Merdeka Curriculum implementation among school supervisors, teachers have difficulties in implementing differentiated learning, lack of ability in using technology-based learning media, and lack of facilities and infrastructure; 3) Teacher suggestions on the challenges in implementing the Merdeka Curriculum include: unifying the understanding of school supervisors regarding the implementation of the Merdeka Curriculum, providing training for teachers to work on learning tools, and providing special training according to subject matter, and providing adequate facilities and infrastructure, such as library to support the implementation of Merdeka Curriculum